Jogos de solicitação tático-técnica no ensino médio : estudo de caso de uma metodologia para o ensino do futsal - Fávero, Givanildo (2016)
This research, based on a pedagogical concern caused by the contact with a methodology for the teaching of futsal, occurred within a school context, through a punctual intervention in the curriculum component of Physical Education, having as initial inquiry: what do high school students submitted to the experience of games of tactical-technical request reveal? The central objective was to understand how the students of the public school Major Otávio Pitaluga, from the city of Rondonópolis- MT, play against the games of tactical-technical request applied to futsal. In this sense, other objectives that guided this study emerged: to verify the influence of the JSTT in the learning of the high school students of EEMOP; to Investigate if there is collective work by the students to deal with situations-problems presented by the JSTT; to observe how JSTT can contribute to decision making; to analyze whether the JSTT promote motivation and interest in educational sports; and experience situations with JSTT with mixed formations (coeducational classes) in order to verify the levels of student's resourcefulness and acceptability. After the reading and the elaboration of the theoretical reference, the second stage of the qualitative/descriptive research of Case Study type was carried with a high school first year class of EEMOP, initially composed by 26 students, of whom 9 were female and 17 males, where a series of 15 JSTTs were applied to the teaching of futsal in a period of 4 months (March to June 2016) during Physical Education classes. The data collect was based on the records of the observation matrix and semi-structured interview. The content analysis of the data, allied with the theoretical reference discussions, made it possible to understand that before the JSTT the students involved worked collectively frequently to face situations-problems, with greater communication and action; Improved positioning and movement on the court; Had an increase in autonomous attitudes for decision making; Demonstrated motivation and interest for the educational sport; The students acted with aplomb and acceptability in attending classes with the presence of the female students.